Cone beam computed tomography and periapical lesions: a systematic review analysing studies on diagnostic efficacy by a hierarchical model. (24th October 2014) - Kruse, C.; Spin‐Neto, R.; Wenzel, A.; Kirkevang, L.‐L.
Abstract Aim To evaluate using a systematic review approach the diagnostic efficacy of CBCT for periapical lesions, focusing on the evidence level of the included studies using a six‐tiered hierarchical model. Methodology The MEDLINE bibliographic database was searched from 2000 to July 2013 for studies evaluating the potential of CBCT imaging in the diagnosis and planning of treatment for periapical lesions. The search strategy was limited to English language publications using the following combined terms in the search strategy: apical pathology or endodontic pathology or periapical or lesion or healing and CBCT or cone beam CT. The diagnostic efficacy level of the studies was assessed independently by four reviewers. Results The search identified 25 publications that qualitatively or quantitatively assessed the use of CBCT for the diagnosis of periapical lesions, in which the methodology/results comprised at least one of the following parameters: the methods, the imaging protocols or qualitative/quantitative information on how CBCT influenced the diagnosis and/or treatment plan. Conclusion From the assessed studies, it can be concluded that although there is a tendency for a higher accuracy for periapical lesion detection using CBCT compared to two‐dimensional imaging methods, no studies have been conducted that justify the standard use of CBCT in diagnosing periapical lesions. In addition, it should be considered that, at the present time, the efficacy of CBCT as the diagnostic imaging method for periapical lesions has been assessed merely at low diagnostic efficacy levels.